Array of Synthetic Oligonucleotides to Generate Unique Multi-Target Artificial Positive Controls and Molecular Probe-Based Discrimination of Liposcelis Species - Arif, Mohammad; Opit, George; Mendoza-Yerbafría, Abigail; Dobhal, Shefali; Li, Zhihong; Kučerová, Zuzana; Ochoa-Corona, Francisco M (PLoS One, 2015)
Several species of the genus Liposcelis are common insect pests that cause serious qualitative and quantitative losses to various stored grains and processed grain products. They also can contaminate foods, transmit pathogenic microorganisms and cause allergies in humans. The common occurrence of multi-species infestations and the fact that it is difficult to identify and discriminate Liposcelis spp. make accurate, rapid detection and discriminatory tools absolutely necessary for confirmation of their identity. In this study, PCR primers and probes specific to different Liposcelis spp. were designed based on nucleotide sequences of the cytochrome oxidase 1 (CO1) gene. Primer sets ObsCo13F/13R, PeaCo15F/14R, BosCO7F/7R, BruCo5F/5R, and DecCo11F/11R were used to specifically detect Liposcelis obscura Broadhead, Liposcelis pearmani Lienhard, Liposcelis bostrychophila Badonnel, Liposcelis brunnea Motschulsky and Liposcelis decolor (Pearman) in multiplex endpoint PCRs, which amplified products of 438-, 351-, 191-, 140-, and 87-bp, respectively. In multiplex TaqMan qPCR assays, orange, yellow, red, crimson and green channels corresponding to reporter dyes 6-ROXN, HEX, Cy5, Quasar705 and 6-FAM specifically detected L. obscura, L. brunnea, L. bostrychophila, L. pearmani and L. decolor, respectively. All developed primer and probe sets allowed specific amplification of corresponding targeted Liposcelis species. The development of multiplex endpoint PCR and multiplex TaqMan qPCR will greatly facilitate psocid identification and their management. The use of APCs will streamline and standardize PCR assays. APC will also provide the opportunity to have all positive controls in a single tube, which reduces maintenance cost and labor, but increases the accuracy and reliability of the assays. These novel methods from our study will have applications in pest management, biosecurity, quarantine, food safety, and routine diagnostics.
Keywords: oligonukleotidové sondy; Animals; Oligonucleotide Probes; Insect Proteins; DNA; Insect Control; zvířata; respirační komplex IV; Oligonucleotides; hmyz; Electron Transport Complex IV; oligonukleotidy; polymerázová řetězová reakce; Insecta; hmyzí proteiny; Polymerase Chain Reaction; dezinsekce